Multiparametric Magnetic Resonance Imaging Characteristics of Prostate Tuberculosis - Cheng, Yue; Huang, Lixiang; Zhang, Xiaodong; Ji, Qian; Shen, Wen (Korean journal of radiology, 2015)
To describe the multiparametric magnetic resonance imaging (MRI) appearance of prostate tuberculosis. Six patients with prostate tuberculosis were analyzed retrospectively. The mean age of the patients was 60.5 years (range, 48-67 years). The mean prostate specific antigen concentration was 6.62 ng/mL (range, 0.54-14.57 ng/mL). All patients underwent a multiparametric MRI examination. The histopathological results were obtained from biopsies in four men and from transurethral resection of the prostate in two men after the MRI examination. Nodular (33%, 2/6 patients) and diffuse lesions (67%, 4/6 patients) were seen on MRI. The nodular lesions were featured by extremely low signal intensity (similar to that of muscle) on T2-weighted imaging (T2WI). The T2WI signal intensity of the diffuse lesions was low but higher than that of muscle, which showed high signal intensity on diffusion weighted imaging and low signal intensity on an apparent diffusion coefficient map. MR spectroscopic imaging of this type showed a normal-like spectrum. Abscesses were found in one patient with the nodular type and in one with the diffuse type. The appearance of prostate tuberculosis on MRI can be separated into multiple nodular and diffuse types. Multiparametric MRI may offer useful information for diagnosing prostate tuberculosis.